Design a Goods Delivery Service Application Using React Native - Adek Siti Nurhalizah; Geovanne Farell (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
Goods delivery services are a type of service for entrusting the purchase of goods from a customer to be purchased by the Jastiper for all the desired orders and needs. To run a consignment service business, you need an application that supports it to make it easier for consumers to entrust the purchase of goods. The choice of the React Native Framework in creating a goods delivery service application is under the needs of the project to be developed, where the programming language is easier to understand and can produce two forms of output, namely in Android or iOS. The Goods Delivery Services application aims to facilitate users in offering services and searching for goods, making it easier for service providers (jastipers) to find customers and making it easier for service users (customers) to find entrusted service providers who can entrust the purchase of the goods they need. The waterfall method is used in designing applications starting with specification of user needs then planning, modeling, construction, deployment, and support for the resulting complete software. The result of designing a goods delivery service application is a mobile application for jastipers and customers, and a web application for admins and operators. The development tools used consist of Visual Studio Code, JavaScript, and XAMPP.